Presidential Decree Law No. 17/2015 Amending Some Provisions Of Companies Law, General Sales Tax Law, Investment Guarantees, And Incentives Law, And Income Tax Law = قرار رئيس الجمهورية بالقانون رقم 17 لسنة 2015 بتعديل قانون الشركات وقانون الضريبة على المبيعات وقانون الاستثمار وقانون الضرائب على الدخل / presidency - Egypt. presidency (2025)
Presidential Decree-Law No. 17 of 2015 Amending Some Provisions of Companies law general sales tax law and income tax law قرار رئيس الجمهورية بالقانون رقم 17 لسنة 2015 بتعديل قانون الشركات وقانون الضريبة على المبيعات وقانون الاستثمار وقانون الضرائب على الدخل